A triboelectric nanogenerator based on flexible zwitterionic ionic conductive hydrogel for running training monitoring - Yang Yang; Yuanji Zhao (Materials & Design, 2024)
Recently, wearable electronic devices based on ionic conductive hydrogel have received much attention. However, the hydrogels currently reported face challenges in terms of fatigue strength and mechanical properties. Hence, we designed a flexible zwitterionic ionic conductive (F–Zn) hydrogel for the strain sensor and triboelectric nanogenerator (F-TENG). According to the results, the open-circuit voltage (Voc) of F-TENG can reach 245.54 V. The short-circuit current (Isc) and transfer charge (Qsc) of F-TENG can arrive at 9.16 µA and 81.16 nC. As the self-powered pressure sensor, two linear sensing regions of F-TENG can be observed, with sensing sensitivities of 5.9 kPa−1 and 2.05 kPa−1, respectively. In the meantime, when the F-Zn hydrogel serves as strain sensor, the Gauge Factor (GF) can arrive at 0.99. It's important to note that F-TENG can complement the static sensing of the F-Zn hydrogel strain sensor by having application value in dynamic motion sensing. Comprehensive monitoring of running movements is achievable by two sensors with different working mechanisms, paving the way for multifunctional running hydrogel sensors.